Relationship Husband Support With Cervic Cancer Prevention Behavior To Women Of Young Married Age In The Village Tuntungan I Pancur Batu In 2022 - Friska Sri Handayani Br Ginting; Helinida Saragih; Henny T Simanjuntak (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Cervical cancer prevention behavior is an action taken to prevent cervical cancer by avoiding risk factors. The behavior of women in conducting the examination is influenced by the husband's support which shows the husband's understanding of his wife providing motivation, support, and increasing feelings of security in a relationship. This study aims to determine the relationship between husband's support and cervical cancer prevention behavior on young married women in Tuntungan Pancur Batu Village in 2022. The research design is a cross sectional population in this study as many as 85 people. The sampling technique is purposive sampling. The results of the study obtain bad husband support (95.3%) and bad cervical cancer prevention behavior as much as (84.7%). The results of the Chi Square statistical test obtain a P-value = 0.048 (p>0.05) so it is concluded that there is a significant relationship between husband's support and cervical cancer prevention behavior in young married women at Tuntungan Village I Pancur Batu. It is hoped that women can improve cervical cancer prevention behavior by increasing knowledge and self-awareness.